2015
DOI: 10.1074/jbc.m115.687558
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Functional Roles of Amino Acid Residues in Acceptor-binding Subsite +1 in the Active Site of the Glucansucrase GTF180 from Lactobacillus reuteri 180

Abstract: ␣-Glucans produced by glucansucrase enzymes hold strong potential for industrial applications. The exact determinants of the linkage specificity of glucansucrase enzymes have remained largely unknown, even with the recent elucidation of glucansucrase crystal structures. Guided by the crystal structure of glucansucrase GTF180-⌬N from Lactobacillus reuteri 180 in complex with the acceptor substrate maltose, we identified several residues (Asp-1028 and Asn-1029 from domain A, as well as Leu-938, Ala-978, and Leu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 46 publications
2
60
0
Order By: Relevance
“…A second difference is Asp991 of L. fermentum NCC 2970 GtfB; it replaces the conserved Asn present in GSs and most GtfB-like 4,6-α-GTases. In the GS of L. reuteri 180 this residue was found to be essential for activity and linkage specificity31. The preceding Asp is conserved in L. fermentum GtfB (Asp 990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second difference is Asp991 of L. fermentum NCC 2970 GtfB; it replaces the conserved Asn present in GSs and most GtfB-like 4,6-α-GTases. In the GS of L. reuteri 180 this residue was found to be essential for activity and linkage specificity31. The preceding Asp is conserved in L. fermentum GtfB (Asp 990).…”
Section: Resultsmentioning
confidence: 99%
“…However, the lack of 3D structural information and of α1 → 2 and α1 → 3 synthesizing maltodextrins/starch utilizing type of GH70 enzymes has limited our understanding of the structural features determining this different substrate and product specificity. For GSs, the crystal structure of GTF180-ΔN with a bound maltose acceptor combined with site-directed mutagenesis experiments revealed that the linkage specificity is controlled by residues forming the acceptor substrate binding subsites +1/+22029303132. Despite their different domain organization, GtfB, GtfC, and GtfD 4,6-α-GTase enzymes display high conservation in their motifs I to IV, particularly in residues forming the acceptor substrate binding subsites in GSs2326.…”
mentioning
confidence: 99%
“…For that purpose, a better understanding of the dextransucrase structural determinants dictating polymer elongation appears necessary. In the last decades, sequence analyses and X-Ray 3D-structure characterizations allowed pointing some amino acid residues involved in linkage specificity [6][7][8][9][10][11]. However, less is known on the enzyme structural determinants controlling the polymer size.…”
Section: Introductionmentioning
confidence: 99%
“…Residues in homology regions I-IV in domain A are critical for linkage specificity determination of glucansucrase enzymes, as shown in previous mutagenesis studies 15 39 40 41 42 43 . Moreover, residues from domain B have been shown to shape the acceptor binding sites and hence determine the linkage specificity 10 16 41 44 45 . The amino acid sequences of these regions in GTFO and GTFA were compared by alignment with the other glucansucrase enzymes from LAB ( Fig.…”
Section: Resultsmentioning
confidence: 99%